Agricultural Technology Transfer Methods and Adaptability of Rural Farmers in Ikwerre Local Government Area of Rivers State - A.U. Nnodim; Raji W.I (PT FORMOSA CENDEKIA GLOBAL, 2023)
The study investigated that agricultural technology transfer methods and adaptability of rural farmers in Ikwerre Local Government Area of Rivers State. The sample size used for the study was 120 rural farmers. Cluster random sampling was used to select ten (10) rural women farmers from 12communities of Ikwerre Local Government Area. Two instruments for data collection were used in the study. One was “Agricultural technology transfer methods questionnaire”. The second research instrument was “Farmers Adaptability to Agricultural Technology Questionnaire”. The study found that farmer-to-farmer method and household method of transferring agricultural technologies have strongest and significant relationship with farmers’ adaptability to new technological innovations than other methods. It was recommended that government should provide adequate fund for extension workers basically for encouraging household, farmer-to-farmer method in transferring agricultural innovation.